2019
DOI: 10.1002/joa3.12283
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive stereotactic radioablation for the treatment of atrial fibrillation: First‐in‐man experience

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.Tweet: First-in-man treatment of atrial fibrillation using noninvasive stereotactic radioablation demonstrates feasibility. Abbreviations: AF, atrial fibrillation; AV, atrioventricular; CT, computed tomography; DOAC, direct oral anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 22 publications
1
54
0
2
Order By: Relevance
“…Recently, Monroy et al and Qian et al reported the human experience of non-invasive stereotactic radioablation for the treatment of atrial fibrillation. 19 In this study, two patients with drugrefractory AF were treated with radiation with 25-Gy single fraction. Although they reported no procedure-related complications, inevitable exposure to critical structures, such as the esophagus, may have been a major concern because AF is generally not directly related to sudden death.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Monroy et al and Qian et al reported the human experience of non-invasive stereotactic radioablation for the treatment of atrial fibrillation. 19 In this study, two patients with drugrefractory AF were treated with radiation with 25-Gy single fraction. Although they reported no procedure-related complications, inevitable exposure to critical structures, such as the esophagus, may have been a major concern because AF is generally not directly related to sudden death.…”
Section: Discussionmentioning
confidence: 99%
“…One patient had recurrence of atrial fibrillation (now persistent) after 6 months of follow-up; the other remained arrhythmia free after 2 years of follow-up. 49 Two case reports, Haskova et al 50 and Zeng et al, 51 lung changes consistent with radiation-induced pneumonitis. 27 These changes resolved by the 12 month follow-up examination.…”
Section: Encore-vt the Electrophysiology-guided Non-invasive Cardiacmentioning
confidence: 94%
“…48 The first report of STAR for pulmonary vein isolation for AF was published by Qian et al 2019. 49 Results from two ambulatory patients with paroxysmal atrial fibrillation despite ≥1 antiarrhythmic medications who had not previously undergone invasive catheter ablation were reported. An internal fiduciary marker was placed transvenously and attached to the interatrial septum for treatment planning and respiratory motion tracking.…”
Section: Encore-vt the Electrophysiology-guided Non-invasive Cardiacmentioning
confidence: 99%
“…У второго пациента за время наблюдения нарушений ритма не зафиксировано, весь период наблюдения принимался пропафенон (450 мг/сут). Отдаленных осложнений процедуры не отмечалось [24].…”
Section: клиническое применение и исследования систем для роботическоunclassified